TRIBAL TEACHERS IN PUBLIC AND PRIVATE SCHOOLS: A STUDY OF THEIR JOB SATISFACTION AS RELATED TO CERTAIN SOCIO-PSYCHOLOGICAL FACTORS - Jabeen, Sarwat (PEOPLE: International Journal of Social Sciences, 2018)
Background: Educational institutions where people are employed for teaching work provide an organizational structure to them. The academic performance of the students in a school depends upon the effective role of teachers, which in turn is dependent upon the job satisfaction of the teachers. It is an admitted fact that both industrial productivity and the well-being of the employees are related to the fact as to how satisfied or dissatisfied employees are on the job.Objective: To examine the differences if any between the teachers of public and private schools on job satisfaction and its allied psychological factors. Materials and Methods:The present study consists of 320 tribal school teachers drawn from high schools located in Ranchi on a stratified random basis. Each teacher were given personal data questionnaire, job satisfaction, anxiety, job involvement, organizational commitment and locus of control scale for assessing their sociological and personality correlates of job satisfaction. Results:Type of school produces significant main effects on job satisfaction. The obtained value is 12.47, which is statistically significant at .01 level of confidence. On the basis of the correlations obtained, it may be concluded that job satisfaction, job involvement, organizational commitment and locus of control are negatively correlated with anxiety, and positivity correlated with each other.